2018
DOI: 10.1038/s41598-018-20491-1
|View full text |Cite
|
Sign up to set email alerts
|

Secretory factors from OP9 stromal cells delay differentiation and increase the expansion potential of adult erythroid cells in vitro

Abstract: Development of in vitro culture systems for the generation of red blood cells is a goal of scientists globally with the aim of producing clinical grade products for transfusion. Although mature reticulocytes can be efficiently generated by such systems, the numbers produced fall short of that required for therapeutics, due to limited proliferative capacity of the erythroblasts. To overcome this hurdle, approaches are required to increase the expansion potential of such culture systems. The OP9 mouse stromal ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Of note, also stromal co-cultures (MS5 or OP9) do not completely result in reticulocyte maturation to erythrocytes ( Giarratana et al, 2005 ; Lu et al, 2008 ). Indeed, a recent study published a characterization of the secretory proteins from OP9, and such studies may eventually point to specific factors to will further facilitating erythropoiesis and possibly reticulocyte maturation ( Trakarnsanga et al, 2018 ). One such extrinsic signal may be transport/exchange regulation of volume control upon circulation-induced shear stress to facilitate reticulocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, also stromal co-cultures (MS5 or OP9) do not completely result in reticulocyte maturation to erythrocytes ( Giarratana et al, 2005 ; Lu et al, 2008 ). Indeed, a recent study published a characterization of the secretory proteins from OP9, and such studies may eventually point to specific factors to will further facilitating erythropoiesis and possibly reticulocyte maturation ( Trakarnsanga et al, 2018 ). One such extrinsic signal may be transport/exchange regulation of volume control upon circulation-induced shear stress to facilitate reticulocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…According to another report, the coculture of adult CD34 + cells with OP9 feeder cells increases the proliferation ability of erythroid cells by delaying erythroid differentiation. 35 We therefore speculated that stromal cell coculture maintains MT erythroblasts in a more immature state than the feeder-free condition, preventing their death as maturation proceeds. MT erythroblasts failed to synthesize heme and exhibited maturation defects with ring sideroblast formation in contrast to WT erythroblasts ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we observed that OP9 cells impaired patient ILC2 functions, since their type-2 cytokine secretion was dramatically reduced. One can speculate that OP9-secreted factors 59 might directly affect cytokine secretion. Nevertheless, in line with previous observations, 49 we also observed that the addition of OP9 cells restrains ILC2 plasticity.…”
Section: Discussionmentioning
confidence: 99%